2019
DOI: 10.1080/10255842.2019.1582033
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of ciliary propulsion of an electrically-conducting Johnson-Segalman physiological fluid in a channel with slip

Abstract: Ti t l e M a t h e m a tic al m o d elli n g of cilia ry p r o p ul sio n of a n el e c t ric ally c o n d u c ti n g Joh n s o n-S e g al m a n p hy siolo gic al flui d in a c h a n n el wi t h slip

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Non-Newtonian ciliated metachronal propulsion has also been examined by a variety of investigators. Manzoor et al [20] used the Blake elliptic cilia model to study magnetohydrodynamic metachronal slip flow of Johnson-Segalman fluids in a channel. They derived perturbation solutions and showed that with greater viscous force relative to elastic force (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Newtonian ciliated metachronal propulsion has also been examined by a variety of investigators. Manzoor et al [20] used the Blake elliptic cilia model to study magnetohydrodynamic metachronal slip flow of Johnson-Segalman fluids in a channel. They derived perturbation solutions and showed that with greater viscous force relative to elastic force (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…whereμ B the plastic viscosity, Υ the volume fraction density, ξ ij the deformation rate of component, and y s the yield stress, π denotes the second invariant tensor of ξ ij , π Υ represents the critical value comprises on the non-Newtonian fluid model. The Mathematical expression for the envelope of the cilia tips reads as [31,32]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…where k = 2π/λ, z 0 describes the reference location of the cilia, the non-dimensional parameter φ, which combines with b 0 (mean radius of the outer tube) in the form of b 0 φ and represents the amplitude of metachronal wave, λ is the metachronal wavelength, c the velocity, and α describes the measure of the eccentricity of the elliptical motion. The vertical and axial velocities are evaluated as [31,32]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…Singh et al [15] applied the short memory Walters-B viscoelastic fluid model to study combined free and forced convective in reactive electrically conducting vertical channel transport. Further studies have implemented the Saffman dusty fluid-particle model [16], Bingham viscoplastic model [17], a third grade viscoelastic Reiner-Rivlin fluid [18] and more recently the Johnson-Segalman elastic-viscous model [19]. All these studies identified a significant modification in heat and momentum transfer characteristics with non-Newtonian effects and substantial deviation from Newtonian results.…”
Section: Introductionmentioning
confidence: 99%